Survival of an Alegory: America as Independent, Merchant and Civilized - Oviedo Salazar, Mauricio G. (2015)
The article sheds light on how within the plastic arts, a single allegory is able to suffer a number of changes through the posible routes that it follows in order to survive in different periods and geographical spaces. In this case the allegory is America, and the ways of survival are the contributors of the historical process of construction of three Costa Rican objects, namely: a coin of 1850 containing the figure of an Indian, an industrial Brand of a drugstore that appropriates the design of the aforementioned coin, and a sculpture made around 1905, orginally located on the terrace of a house in San José.